The impact of accounting and tax law concerning borrowing costs on the assessment of the financial leverage effect - Prewysz-Kwinto, Piotr (Wpływ regulacji prawa bilansowego i podatkowego dotyczących kosztów finansowania zewnętrznego na ocenę efektu dźwigni finansowej, 2018)
The aim of this paper is to present the impact of accounting and tax law concerning borrowing costs on the assessment of financial leverage effect. Due to the fact that these legal regulations require, in some cases, the recognition of borrowing costs not in the profit and loss account but in the value of assets, previously used methods for the identification of financial leverage effect do not always allow to draw the correct conclusions. Therefore, the paper proposes the necessary modification
Financial Sciences. Nauki o Finansach, 2018, vol. 23, no. 2, s. 47-59
Keywords: financial leverage effect; borrowing costs; profitability; accounting law; tax law; IAS/IFRS; efekt dźwigni finansowej; koszty finansowania zewnętrznego; rentowność; prawo bilansowe; prawo podatkowe; MSR/MSSF